'Not yet 50/50' – Barriers to the Progress of Senior Women in the Australian Public Service. Issue 4 (December 2014) - Evans, Mark; Edwards, Meredith; Burmester, Bill; May, Deborah
<x xml:space="preserve">Abstract</x> In most countries around the world women remain in the minority when it comes to senior positions in both the public and private sectors. That there are barriers to their progression is not in doubt. What is not well understood is the nature of those barriers and the extent to which they are consciously or unconsciously constructed. Moreover, there has been a stark absence of empirical studies in the field of Australian public administration to investigate these issues and assess the implications. The purpose of this abbreviated article is to help bridge the gap (the full study is published at https://www.wgea.gov.au/sites/default/files/not%20yet%2050%EF%80%A250%20report‐Final%20Version%20for%20print(1)[1].pdf). It does this through a study of the perceptions of senior men and women of the cultural and systemic barriers affecting the recruitment, retention and promotion of senior women in six Australian Commonwealth departments. The article then proposes a range of mitigating strategies for navigating these barriers and achieving and maintaining a better gender balance at the Senior Executive Service level across the Australian Public Service. These strategies are integrated within a systems model of behavioural change which we hope will prove useful to public organizations embarking on diversity reform initiatives.